On the mobilization of domestic resources in oil countries: The role of historical factors - Luc Désiré Omgba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper investigates the sources of variability in the mobilization of domestic tax revenue in oil-producing countries. It argues that the type of natural resources exploited during colonial rule can affect the contemporary levels of domestic tax revenue in oil countries. We test this conjecture by regressing non-oil tax revenue on a proxy of extractive capacity, which is the distance between the date of the beginning of oil production and the date of a country's political independence. The results show that this proxy of extractive capacity positively affects the non-oil tax revenue of oil-producing countries, and these results are robust to various sensitivity checks. The persistence of the pre-existing extractive institutions as well as their subsequent privileged position explain why the elites have no interest in changing this scenario.
Keywords: H20; Q32; N5; 330; tax revenues; oil resources; economic history